The Effectiveness of Rational Emotive Behavior Therapy (REBT) Group Counseling to Reduce Cheating Behavior - Wijayanti, Arni; Sugiharto, Dwi Yuwono Puji; Wibowo, Mungin Eddy (Jurnal Bimbingan Konseling, 2019)
This study aims to analyze the effect of REBT group counseling services (Rational Emotive Behavior Therapy) to reduce the cheating behavior of VIII grade students Public Junior High School 2 Kendal. The experimental research method uses the design of one group pre-post test. The research subjects were VIII grade Public Junior High School 2 Kendal as many as 60 students, with a sample of 7 students selected by purposive sampling technique. Based on the results of t-test analysis is understood that the effectiveness of REBT group counseling (Rational Emotive Behavior Therapy) to reduce cheating behavior between before and after being given treatment (t(7) = 3.925, p < 0.01). This finding confirms that group counseling with reinforcement techniques can be applied to reduce student cheating behavior.